Employer brand building from the inside-out: how employer values contribute to employee engagement - Ferreira, Pedro (2018)
Employer Branding is a concept that is gaining importance within the Human Resources field mainly due to its potential for retaining and attracting talent to boost organisations capabilities and competitiveness. According to the brand management literature, building a brand must start from within, and the employer brand should also function as a reference for a company’s current employees. Thus, taking this assumption into account, the main goal of this paper is to understand how employer branding contributes towards employee engagement. In order to address this research problem the authors based the research on a leading manufacturing company in cosmetics, personal care, beauty, homecare and healthcare products and a major supplier of tinplate and plastic packaging, that is going through a process of employer brand building. Field research developed in two steps. First, the HR department and some members of the Board defined the main attributes of the brand as an employer. Second, a survey was administered to senior managers to assess the level of engagement and how they perceive the employer brand attributes. Data dimensionality was reduced using factor analysis and regression analysis tested the relation of employer brand attributes and employee engagement. Factor analysis revealed three main groups of employer brand attributes: Innovation & Growth, Work Environment and Socially Responsible Practices. Employee engagement is mainly explained by Innovation & Growth attributes. The least relevant group of attributes is Socially Responsible Practices. These results contribute to better understand the relation between employer brand and employee outcomes and the importance of defining and managing employer brand attributes to foster employee engagement.